Fortune's rocks : a novel - Shreve, Anita. 1946 (Back Bay Books/Little, Brown and Company, 2015)
Summary: It is the summer of 1899, and Olympia Biddeford and her parents have retired from the heat of Boston to the coastal resort of Fortune's Rocks. When the celebrated essayist John Haskell is invited to stay, no one foresees the affair that is to follow. What begins as the briefest of silences becomes a relationship that is both passionate and destructive - six short weeks that will shape the rest of their lives.